THE IMPORTANCE OF HYRUDOTHERAPY IN THE TREATMENT OF MIGRAINE - Tilyaxodjayeva Gulbahor Botirovna (Scholar Express Journals, 2023)
This scientific work contains the results of a study conducted in patients with migraine, the effectiveness of hirudotherapy in people with headaches, in particular migraine. The features of the manifestation of migraine from other diseases, as well as the economic costs caused by migraine, are described[1,2,3]
Keywords: Hydrotherapy; migraine; hirudin; costs